Hubungan Problem Solving dan Kecerdasan Emosional Terhadap Hubungan Sosial Siswa - Lianti, Afdha; S, Neviyarni; Nirwana, Herman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
According to experts, problem-solving is a cognitive process that involves identifying problems, gathering information, analyzing them, finding solutions, and practicing these solutions to achieve the desired results. When solving problems, we apply critical thinking, reasoning, and creative problem-solving skills to solve the problem at hand. Therefore, problem-solving is simply the process of producing an effective solution to a problem. Based on research conducted by Helmi Asy'ari, Thesis (2021), Analysis of the Relationship between Collaborative Problem Solving Learning and students' ability to adapt and cooperate. Based on these results, it can be concluded that collaborative problem-solving activities have a positive and strong relationship with the ability to adapt through emotional and cognitive development with the occurrence of macro and somatic cognitive processes. Thus, it can be concluded in various ways that junior high school students' problem-solving skills and their capacity for independent learning are significantly positively correlated when they engage in problem-based learning with light-reflection materials. Novita Dwi Ninggrum's research, The relationship between emotional intelligence and family social support and the social adjustment of adolescent families. The results of the data analysis stated that there was a positive relationship between emotional intelligence and family social support family social adjustment and adolescent social adjustment. The contribution of emotional intelligence and family social support in influencing adolescents' social adjustment is 9.5%.